Internationalization of Malaysian service firms / Mohammadreza Asgari - Asgari, Mohammadreza (2012)
This study aims to investigate the process of the internationalization of firms in the context of Malaysian service industries. Unlike previous research that was limited to a specific theory, this study was inspired from nine theories of internationalization that have been developed since the 1960s and provide useful explanations for the three strategic choices of firms – market selection, entry timing and the choice of entry mode. However, there is no comprehensive theory to explain these strategies. Therefore, this study used different theoretical models to offer a proposed framework for examining the effects of organizational factors on the expansion strategies and investigating the moderating role of the inseparability of services. Although previous research mainly studied the strategies of multinational firms from developed countries, this study focused on Malaysia, as a developing country with a rapid economic growth and an improving position in the global markets. The increasing foreign investment made by Malaysian service firms was a major motive for pursuing this study. To explore the factors that facilitate the expansion of Malaysian service firms, a quantitative method was used by sending a mail survey to an initial sample of 303 service firms listed in the Bursa Saham Malaysia, from which 87 questionnaires were returned as the actual sample. For the data analysis process, a logistic binomial regression technique was used because the dependent variables were defined as a binary variable. To clarify and justify the results of hypotheses testing, each finding was matched with the literature. Based on the results of the study, four models were developed to explain the role of internal factors in shaping the strategies of Malaysian service firms in terms of market selection, the order of entry, the timing of entry and the choice of entry mode. This study made various contributions to the body of knowledge by extending previous theoretical models and examining them in a new context using a quantitative method, considering all internationalization strategies and all service industries. This study can be used as a basis for future research in this field not only in the context of Malaysia but also in other developing countries. It can also be extended to the manufacturing and agriculture sectors. This research has theoretical and practical implications, and its results should be applied by the managers of Malaysian firms and the government agencies to adopt appropriate strategies, enhance the capabilities of firms and provide the required resources for their foreign expansion.